Implementation of the Incoming and Outgoing Mail Management Information System Application at STMIK Neumann Indonesia - Evinitus Sembiring (LKP KARYA PRIMA KURSUS, 2025)
Managing incoming and outgoing mail is a crucial part of administrative activities in higher education institutions, including STMIK Neumann Indonesia. Currently, the process of recording and archiving mail is still done manually, which can potentially cause various problems such as delays in processing mail, lost documents, and difficulties in searching archives. To address these issues, a computerized and integrated Incoming and Outgoing Mail Management Information System application was developed. This application is designed with a web-based approach using the PHP programming language and a MySQL database. The main features developed include managing incoming and outgoing mail, agency data, mail classification, user management, and mail reports. This system is also equipped with an access rights-based login function to maintain data security. Test results show that the application can help administrative processes be faster, more efficient, and well-documented. By implementing this information system, STMIK Neumann Indonesia can improve the effectiveness of administrative services, accelerate the flow of mail disposition, and create a structured and modern digital archiving system.